Identification of vocal and voice disorders - Murugesa Pandiyan, Paulraj, Prof. Madya Dr.; Sazali, Yaacob, Prof. Dr.; Mohd Rizon, Mohammed Juhari, Prof. Dr.; Sivanandam, S. N.; Muthusamy, Hariharan, Dr. (Universiti Malaysia Perlis (UniMAP), 2011)
Organized by Universiti Malaysia Perlis (UniMAP), 25th - 26th October 2007 at Putra Brasmana Hotel, Kuala Perlis, Perlis, Malaysia.